Descrição e difusão de acervo filmográfico: um estudo de caso do Arquivo Público Mineiro - Caio Rosendo de Resende Silva (2023)
The project bases itself on the idea of description and of diffusion, two of the seven biggest archival functions, applied for film archive. The Arquivo Público Mineiro was the institution chosen for the study, due to its consolidated presence in the cultural field and large film archive. The study organizes itself in a way to bring the point of view of authors that produce material about the theme and examples of applications in archives of national reference. The detailing and exemplification are such that anyone, even not having background knowledge in the field of information science, may apply the concepts and ideas developed for the film archive management in their own work in a simple manner. Dealing with the ideas of the initial concepts of description and of diffusion and later specific case of the Arquivo Público Mineiro, the dissertation points out how those processes were accomplished inside of this institution and compares it to the pointed references of cited authors. Collection processes, fundraising and development of impact projects on the collection in addition to pointing out problems and possible solutions found during the study are some of the items presented. Thus, bringing a possible reference for each individual to study their own institution and, if need be, propose the proper changes to be made in each scenario. The study was stimulated by its relevance to the field of Information Science due to little academic production in Portuguese. It also briefly presents conservation notions for the specific case of film archive.